Die oudheid van die letter en die nuutheid van die Gees. Enkele opmerkings oor die Skrif as lewende Woord - P. F. Theron (Acta Theologica)
The antithesis between letter (gramma) and Spirit (pneuma) should be understood within the eschatological contrast between the old passing age and the new eschatological kingdom. The eschatological tension between the old creation and the new re-creation is reflected in the dialectical tension between letter and Spirit. Since the letter is a creation of the Spirit and is at the same time judged by the Spirit, this tension is within the letter itself. Therefore a warning is sounded against identifying the law or the Old Testament as such, with the gramma. The contrast between gramma and pneuma, old and new, permeates the entire Bible (i.e. Old and New Testament). This tension is the work of the Spirit as the auctor primarius of Scripture, through which the “dead letter” is transformed into the living Word. “The new which God works makes itself similar to the old, and thereby makes the old into a parable of the new” (Jüngel). Therefore a pneumatological reading of Scripture implies that the literal sense is taken seriously, since it is from the latter that the meaning (respectively: significance) of the text arises. When, however, the pneuma is rejected the letter becomes not merely dead, but deadly.